Agricultural technology adoption and rural poverty in Ethiopia. (4th April 2023) - Shita, Aynalem; Kumar, Nand; Singh, Seema
Poverty is the major problem of the developing world. Hence, development of the agriculture sector is considered as a pertinent strategy for insuring food security and alleviation of poverty since it is the major source of income for the larger share of the population of developing countries. This article evaluates the poverty reduction effect of agricultural technology in Ethiopia. To achieve its objective primary data has been collected from 400 farm households in Awi zone, Ethiopia. The results were estimated by using propensity score matching technique. The estimated results revealed that adoption of fertiliser and improved seeds resulted in a positive and significant (at 1%) increment on households' per adult consumption expenditure ranging from Birr 1700-1818 but reduces poverty by 18.8%-20.0% based on different matching algorithms. Therefore, the government, financial institutions, and farmers' cooperatives should be coordinated to enhance farmers' adoption of agricultural technologies in order to reduce rural poverty.